Monitoring Near-Surface Soil Water Content Using Air-Launched GPR Techniques. - Kelly, Bridget B.; Schulz, Herry; Crist, Taylor (My University, 2009)
Monitoring soil water content is an important component of responsible resource management. This research focuses on the potential of air-launched ground penetrating radar (GPR) techniques for rapid, high-resolution water content estimation on a regional scale.
Color poster with text, pictures, and graph describing research conducted by Taylor Crist, Bridget Kelly, and Herry Schulz, advised by Katherine R. Grote.
Keywords: Hydrology--Measurement; Posters; Soil moisture--Measurement; Ground penetrating radar